Introduction to Finance - Laureano, L.; Soares, H.; Mota, A.; Barroso, C. (2024)
This book, now in its fourth expanded edition, explains the solutions to several exercises on relevant financial topics, from corporate financial analysis and financial markets, project investment analysis and the corresponding evaluation tools, to the mechanics of time value of money. The restrictions imposed by the intended academic focus lead to a simplification of the included exercises relative to real life, which allows for their resolution in less time. In accordance, we felt the need to complement the exercises with a theoretical overview, in each chapter, of the main financial principles that give support to most decision making in a financial environment. The financial theory must avoid certain deformed ideas and concepts of easy gains and greed that usually are imbedded in the human nature. We focus on providing the fundamentals behind the true financial logic and we add to the exercises practical alerts that complement the conclusions and calculations provided. This edition has been expanded with a new chapter where some of the exercises throughout the book are solved using Excel and where the use of its native or created functions can be learned in practice.